Advanced Methods of Continuum Mechanics for Materials and Structures - Naumenko, Konstantin; Aßmus, Marcus (Advanced Structured Materials, 2016)
This volume presents a collection of contributions on advanced approaches of continuum mechanics, which were written to celebrate the 60th birthday of Prof. Holm Altenbach. The contributions are on topics related to the theoretical foundations for the analysis of rods, shells and three-dimensional solids, formulation of constitutive models for advanced materials, as well as development of new approaches to the modeling of damage and fractures.